2015
DOI: 10.1111/ejn.13076
|View full text |Cite
|
Sign up to set email alerts
|

Gad1 mRNA as a reliable indicator of altered GABA release from orexigenic neurons in the hypothalamus

Abstract: The strength of γ-aminobutyric acid (GABA)-mediated inhibitory synaptic input is a principle determinant of neuronal activity. However, because of differences in the number of GABA afferent inputs and the sites of synapses, it is difficult to directly assay for altered GABA transmission between specific cells. The present study tested the hypothesis that the level of mRNA for the GABA synthetic enzyme glutamate decarboxylase (GAD) can provide a reliable proxy for GABA release. This was tested in a mouse hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 46 publications
(71 reference statements)
2
25
0
Order By: Relevance
“…Thus, the expression of Gad1 can be a reliable indicator of terminal GABA release, as was recently shown to be the case in AgRP neurons (Dicken et al . ). In AgRP neurons, fasting increased the expression of Gad1 and enhanced the readily‐releasable pool of GABA from AgRP neurons, whereas the inhibition of GAD activity decreased GABA release.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Thus, the expression of Gad1 can be a reliable indicator of terminal GABA release, as was recently shown to be the case in AgRP neurons (Dicken et al . ). In AgRP neurons, fasting increased the expression of Gad1 and enhanced the readily‐releasable pool of GABA from AgRP neurons, whereas the inhibition of GAD activity decreased GABA release.…”
Section: Discussionmentioning
confidence: 97%
“…One study did examine GABA release from AgRP neurons in response to caloric restriction and found that Gad1 mRNA and GABA release was increased under this condition, which correlated well with increased GABA release from these cells (Dicken et al . ). This is consistent with the expected general increase in AgRP neuron activity when the animal is in a state of hunger (Hahn et al .…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Liver [74] Sprague-Dawley rats [11,14] is in turn involved in appetite regulation. [88,89] Also, offspring of rat dams fed methyl (folate and vitamin B 12 )-deficient diets presented with NAFLD following postnatal consumption of HFD. [90] Gene transcription analysis revealed a significant increase in the expression of nuclear factor B (NF B) and TGF-1.…”
Section: Maternal Methyl Donor Nutrients and Cvd Risk Factors In Offsmentioning
confidence: 99%